Dario tigris and Dario melanogrammus, two new species of miniature chameleon fishes from northern Myanmar (Teleostei: Badidae) - Britz, Ralf; Kullander, Sven; Rüber, Lukas (Zootaxa, 2022)
Dario tigris, new species, is described from mountain streams south of Mogaung, in the Ayeyarwaddy River basin, Myanmar. It differs from congeneric species by its unique colour pattern, which consists of a series of eight straight vertical bars, the first two of which in males are ash-grey and the subsequent six are orange-red in life, combined with a series of small black spots arranged in three to four rows dorsolaterally on the head and nape. It differs further from its close relative Dario hysginon, with which it may occur syntopically, by fewer dorsal-fin spines (modally 14 vs modally 15), and fewer vertebrae (modally 12+12=24 vs modally 12+13= 25). Dario melanogrammus, new species, is another barred Dario from the Chindwin River basin. It differs from all other species of the genus by its zigzagging dark vertical bars; amongst Myanmar species, it can be further distinguished from D. hysginon and D. tigris by more vertebrae (modally 26 vs 25 in D. hysginon, and 24 in D. tigris).